(untitled) (International Journal of Physiotherapy, 2025)
Background: This case study aimed to assess the efficacy of posterior oblique chain activation combined with load management strategies in the rehabilitation of gluteal tendinopathy in a badminton player, focusing on improvements in functional recovery and pain reduction. Case Summary: A 36-year-old male Badminton player, experiencing chronic lateral hip pain for 3 months, was diagnosed with gluteal tendinopathy. The patient underwent a structured rehabilitation program over 8 weeks, with a rehabilitation protocol that focused on activating the posterior oblique chain to enhance kinetic chain stability, alongside a progressive load management plan to promote tissue healing and strength. Outcome measures included the Single-Leg Squat (SLS) test to evaluate balance and stability, as well as the Victorian Institute of Sport Assessment– Gluteal Tendinopathy (VISA-G) questionnaire for functional capacity, and the Numerical Pain Rating Scale (NPRS) for pain assessment. Outcome metrics were documented at the initial evaluation (week 0) and subsequently at week 16, corresponding to two months post-treatment conclusion. Results: After therapeutic interventions, at week 16, the FPPA was 6.7º, the pain score on the NPRS was 2/10, and the VISA-G Questionnaire score was 73/100. There was a marked increase in frontal plane stability, with a difference from baseline of 13.6º to 6.7º of FPPA at week 16, and a significant reduction in pain score (NPRS) from baseline, from 7 to 2 points. In terms of function and disability, there is a marked difference from baseline, as indicated by the 34 to 73 score on the VISA-G Questionnaire. Conclusion: The combination of posterior oblique chain activation, progressive load management, and targeted rehabilitation effectively reduced pain, improved functional capacity, and significantly enhanced dynamic stability in this case of gluteal tendinopathy. This provides valuable insight and paves the way for future research to design robust treatment protocols and refine evaluation methodologies.